Preparation method and application of sodium ion battery negative electrode material
By using phenolic resin carbon microspheres as the negative electrode material for sodium ion batteries, the problem of insufficient reversible specific capacity and cycle stability of sodium ion batteries in the prior art is solved, and the effects of high reversible specific sodium storage capacity, good cycle stability and excellent rate performance are achieved.
Patent Information
- Application Number
- CN202411684146.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
AI Technical Summary
The negative electrode materials of existing sodium ion batteries still have room to improve in terms of reversible specific capacity and cycle stability, especially in the application of carbon-based materials, there are problems such as volume expansion and collapse.
Phenolic resin carbon microspheres were used as the negative electrode material for sodium ion batteries. Phenolic compounds, aldehyde compounds, water, and catalysts were mixed to form phenol-aldehyde sol, and reacted with a mixed solution of surfactant and cyclohexane to form gel microspheres and then carbonized to prepare phenolic resin carbon microspheres with high reversible sodium storage capacity and good cycle stability.
The reversible specific capacity and cycle stability of the sodium ion battery are improved, and the phenolic resin carbon microspheres have small particle size, small specific surface area and low true density. They are suitable as the negative electrode material for sodium ion battery and have excellent rate performance.
Smart Images

Figure BDA0005149036510000091 
Figure BDA0005149036510000092 
Figure BDA0005149036510000101
Abstract
Description
Technical Field
[0001] The invention belongs to the application field of sodium ion battery electrode materials, and specifically relates to a preparation method and application of a sodium ion battery negative electrode material based on phenolic resin carbon microspheres. Background Art
[0002] At present, the negative electrode materials widely used in sodium ion batteries are mainly carbon-based negative electrode materials. Polymer-based carbon microspheres have high structural adjustability and isotropic spherical surface, which is conducive to the embedding and extraction of sodium ions in the electrolyte from all directions, effectively alleviating the volume expansion and collapse caused by the embedding and extraction of sodium ions in anisotropic electrode materials. It is a good type of negative electrode material for sodium ion batteries. In addition, the spherical morphology can obtain highly densely stacked electrodes, which is extremely beneficial to improve the quality and volume energy density of the battery. Phenolic resin-based carbon microspheres are a common polymer-based carbon microspheres. The raw materials are cheap, the source is abundant, the residual carbon rate is high, and the toxicity is low. At present, phenolic resin-based carbon microspheres with good performance can be prepared by morphology control, but as a negative electrode material for sodium ion batteries, there are few related reports, and the reversible specific capacity and cycle stability of sodium ion batteries still need to be further improved. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides a method for preparing a negative electrode material for a sodium ion battery based on phenolic resin carbon microspheres, wherein the phenolic resin carbon microspheres as a negative electrode material for a sodium ion battery have a high reversible specific capacity and good cycle stability.
[0004] In the first aspect of the present invention, the present invention provides a method for preparing phenolic resin carbon microspheres, comprising the following steps:
[0005] mixing a phenolic compound, an aldehyde compound, water and a catalyst to form a phenol-aldehyde sol;
[0006] mixing a surfactant and cyclohexane to form a mixed solution;
[0007] The mixed solution is reacted with phenol-formaldehyde sol at a reaction temperature of 25 to 100° C. for a reaction time of 36 to 200 hours to form gel microspheres, which are then dried;
[0008] The dried gel microspheres are carbonized to form phenolic resin carbon microspheres.
[0009] The preparation method is simple to operate, and phenolic compounds and aldehyde compounds form phenol-formaldehyde polymers under the catalytic action of a catalyst. Cyclohexane is a dispersion medium of a surfactant, and has good compatibility with a surfactant. Under the action of a surfactant, the reaction surface energy is reduced, which helps to form gel microspheres of phenolic resin. Therefore, when the mixed solution formed by the surfactant and cyclohexane is reacted with the phenol-formaldehyde sol, the phenolic compounds and aldehyde compounds can undergo a cross-linking reaction in a specific confined space, and the reaction surface energy is reduced, so that the polymerization reaction of the phenolic compounds and the aldehyde compounds is more sufficient, which is conducive to forming gel microspheres. Carbon microspheres are then formed after carbonization treatment. Thus, the phenolic resin carbon microspheres of the present invention will have a higher reversible specific sodium storage capacity, good cycle stability and rate performance as a negative electrode material for a sodium ion battery.
[0010] In some embodiments, the phenolic compound includes at least one of resorcinol and phloroglucinol.
[0011] In some embodiments, the drying process is drying at room temperature and pressure.
[0012] In some embodiments, a surfactant and cyclohexane are mixed to form a mixed solution, and the control parameters are:
[0013] (1) The speed during mixing is 50-1000 r / min;
[0014] (2) The volume ratio of surfactant to cyclohexane is (1:9) to (1:49).
[0015] In some embodiments, the aldehyde compound includes at least one of formaldehyde, benzaldehyde, and acetaldehyde.
[0016] In some embodiments, in the phenol-formaldehyde sol, the molar ratio of the phenol compound, the aldehyde compound, the deionized water and the catalyst is 1:2:20:(0.001-0.05).
[0017] In some embodiments, in the reaction of the mixed solution with the phenol-formaldehyde sol, the volume ratio of the mixed solution to the phenol-formaldehyde sol is 3:1.
[0018] In some embodiments, the dried gel microspheres are subjected to a carbonization reaction to form phenolic resin carbon microspheres, and the temperature of the carbonization reaction is 1000-1600° C. and the time is 2-8 hours.
[0019] In a second aspect of the present invention, the present invention provides a phenolic resin carbon microsphere obtained by the preparation method of the first aspect, and the phenolic resin carbon microsphere satisfies at least one of the following:
[0020] (a) The specific surface area of phenolic resin carbon microspheres is 2 to 10 m 2 / g;
[0021] (b) The true density of phenolic resin carbon microspheres is 1.5-1.9 g / cm 3 ;
[0022] (c) The particle size of phenolic resin carbon microspheres is 2 to 15 μm.
[0023] The phenolic resin carbon microspheres of the present invention have a small specific surface area, low density and small particle size, indicating that the carbon microspheres have a rich closed-pore structure and are suitable as negative electrode materials for sodium ion batteries. The carbon microspheres with a small specific surface area have less surface reaction when the battery is first charged, avoiding excessive consumption of positive electrode sodium ions and resulting in a decrease in the first efficiency. The presence of closed pores provides abundant storage sites for the embedding and de-embedding of sodium ions, especially when the true density is 1.6 to 1.8 g / cm 3 When the sodium ion storage capacity is increased, the phenolic resin carbon microspheres can effectively increase the sodium ion storage capacity. Therefore, the phenolic resin carbon microspheres as the negative electrode material of the sodium ion battery have a high reversible specific sodium storage capacity, good cycle stability and rate performance.
[0024] In the third aspect of the present invention, the present invention provides a negative electrode material for a sodium ion battery, comprising the phenolic resin carbon microspheres obtained by the preparation method of the first aspect, or comprising the phenolic resin carbon microspheres of the second aspect.
[0025] Therefore, the sodium ion battery negative electrode material of the present invention can significantly improve the reversible specific capacity and cycle stability of the battery.
[0026] Compared with the prior art, the present invention has the following beneficial technical effects:
[0027] (1) The phenolic resin carbon microspheres of the present invention have structural characteristics such as small particle size, small specific surface area, and low true density, and can be used as negative electrode materials for sodium ion batteries, and have high reversible specific capacity, good cycle stability and rate performance.
[0028] (2) The method for preparing phenolic resin carbon microspheres of the present invention is simple to operate. The microsphere morphology can be kept intact by only using a normal pressure and room temperature drying method. The density is high after shrinkage. It has the advantages of simple preparation process, low cost, and easy control of morphology and structure.
[0029] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0031] Figure 1 is a scanning electron microscope (SEM) image of the phenolic resin carbon microspheres prepared in Example 1 of the present invention;
[0032] Figure 2 is a particle size distribution diagram of phenolic resin carbon microspheres prepared in Example 1 of the present invention;
[0033] Figure 3 This is a cycle performance diagram of the phenolic resin carbon microspheres prepared in Example 1 of the present invention when used as the negative electrode material of a sodium ion battery;
[0034] Figure 4 This is a rate performance diagram of the phenolic resin carbon microspheres prepared in Example 1 of the present invention when used as the negative electrode material of a sodium ion battery;
[0035] Figure 5 is a particle size distribution diagram of phenolic resin carbon microspheres prepared in Example 2 of the present invention;
[0036] Figure 6 3 is a particle size distribution diagram of phenolic resin carbon microspheres prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0037] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0038] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0039] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0040] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0041] As used herein, the term "carbon microspheres" or "microspheres" refers to the "phenolic resin carbon microspheres" of the present invention.
[0042] In a first aspect of an embodiment of the present invention, the present invention provides a method for preparing phenolic resin carbon microspheres, comprising the following steps:
[0043] mixing a phenolic compound, an aldehyde compound, water and a catalyst to form a phenol-aldehyde sol;
[0044] mixing a surfactant and cyclohexane to form a mixed solution;
[0045] The mixed solution is reacted with phenol-formaldehyde sol at a reaction temperature of 25 to 100° C. for a reaction time of 36 to 200 hours to form gel microspheres, which are then dried;
[0046] The dried gel microspheres are carbonized to form phenolic resin carbon microspheres.
[0047] At present, phenolic resin carbon microspheres are mostly prepared by suspension, emulsion, and reverse emulsion polymerization using a phenol and formaldehyde synthesis system. However, the morphology of the phenolic resin carbon microspheres prepared by the above synthesis methods is difficult to control, the synthesis conditions and process are relatively complex, and the cost is high. Therefore, it is urgent to further improve the synthesis process and prepare phenolic resin carbon microspheres with narrow particle size distribution and easily controllable morphology as negative electrode materials for sodium ion batteries through simple experimental methods.
[0048] The preparation method of the embodiment of the present application is simple to operate. The phenolic compound and the aldehyde compound undergo a polymerization cross-linking reaction under the catalytic action of the catalyst to form a phenol-formaldehyde polymer. Cyclohexane is a dispersion medium for the surfactant, and has good compatibility with the surfactant. Under the action of the surfactant, the reaction surface energy is reduced, which helps to form gel microspheres of phenolic resin. Therefore, when the mixed solution formed by the surfactant and cyclohexane is reacted with the phenol-formaldehyde sol, the phenolic compound and the aldehyde compound can undergo a cross-linking reaction in a specific confined space, and the reaction surface energy is reduced, so that the polymerization reaction of the phenolic compound and the aldehyde compound is more sufficient, which is conducive to the formation of gel microspheres. When the reaction temperature is 25 to 100 ° C, good reaction activity and reaction speed can be maintained, the chain grows normally, the size of the carbon microspheres is easy to control and relatively uniform, and the internal pores are formed normally, which is conducive to storage. After the reaction is completed, the surfactant in the reaction product is removed and dried. The gel microspheres after drying are then subjected to carbonization reaction to form phenolic resin carbon microspheres. The gel microspheres can shrink rapidly in a dry state, reducing their surface area, and then further shrink or even close the pores through carbonization reaction, converting the visible pores on the surface of the carbon microspheres into internal closed pores, further increasing the porosity inside the carbon microspheres, which is beneficial to increasing the sodium storage capacity.
[0049] As an example, the reaction temperature is 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.
[0050] As an example, the reaction time is 36 h, 56 h, 76 h, 96 h, 116 h, 136 h, 156 h, 176 h, 196 h, 200 h, etc.
[0051] In some embodiments of the present invention, the mixed solution is reacted with the phenol-formaldehyde sol at a reaction temperature of 25 to 48° C. for a reaction time of 72 to 120 hours, thereby further increasing the pores inside the carbon microspheres, which is beneficial to increasing the sodium storage capacity.
[0052] As an example, the reaction temperature is 25°C, 30°C, 35°C, 40°C, 45°C, 48°C, etc.
[0053] As an example, the reaction time is 72 h, 82 h, 92 h, 102 h, 112 h, 120 h, etc.
[0054] In some embodiments of the present invention, the phenolic compound includes at least one of resorcinol and phloroglucinol.
[0055] Resorcinol and phloroglucinol have high hydroxyl content and high activity, which can easily promote the reaction, shorten the reaction time and improve the efficiency.
[0056] In some embodiments of the present invention, the drying process is drying at room temperature and pressure.
[0057] The process of drying at room temperature and pressure can avoid the generation of shrinkage internal stress, thereby avoiding the fragmentation and deformation of the carbon microspheres, so that they still maintain a good spherical morphology, closed-cell structural characteristics and three-dimensional cross-linked structure. At the same time, drying at room temperature and pressure has the advantage of a large shrinkage rate, which can keep the morphology of the carbon microspheres intact and have a high density after shrinkage. Therefore, drying at room temperature and pressure has the advantages of simple preparation process, low cost, and easy control of morphology and structure.
[0058] In some embodiments of the present invention, a surfactant and cyclohexane are mixed to form a mixed solution, and the control parameters are:
[0059] (1) The rotation speed during mixing is 50 to 1000 r / min; further, the rotation speed is 100 to 500 rpm / min.
[0060] (2) The volume ratio of the surfactant to the cyclohexane is (1:9) to (1:49). Further, the volume ratio is (1:15) to (1:30).
[0061] When the rotation speed during mixing is 50-1000 rpm / min, it is conducive to good dispersion of the surfactant, has no obvious adverse effect on the particle size of the microspheres, and does not cause energy waste.
[0062] As an example, the rotation speed is 50 rpm / min, 150 rpm / min, 250 rpm / min, 350 rpm / min, 450 rpm / min, 550 rpm / min, 650 rpm / min, 750 rpm / min, 850 rpm / min, 950 rpm / min, 1000 rpm / min, etc.
[0063] During the preparation process, the surfactant can reduce the surface tension of the droplets and promote uniform nucleation of spheres, resulting in smaller particle size. Adjusting the ratio of surfactant and cyclohexane helps to control the size and distribution of microspheres to achieve the desired microsphere properties.
[0064] As examples, the volume ratios are 1:9, 1:14, 1:19, 1:24, 1:29, 1:34, 1:39, 1:44, 1:49, etc.
[0065] In some embodiments of the present invention, the aldehyde compound includes at least one of formaldehyde, benzaldehyde and acetaldehyde. Further, the aldehyde compound is formaldehyde.
[0066] Formaldehyde, benzaldehyde and acetaldehyde can all undergo polymerization reaction with phenolic compounds to form phenolic resin carbon microspheres. Formaldehyde is the preferred aldehyde reactant for preparing phenolic resin carbon microspheres due to its easy availability, low cost and high reactivity.
[0067] In some embodiments of the present invention, in the phenol-formaldehyde sol, the molar ratio of the phenol compound, the aldehyde compound, the deionized water and the catalyst is 1:2:20:(0.001-0.05).
[0068] The hydroxyl groups in phenolic compounds and aldehyde compounds react to form methylene bridges (-CH2-). When the molar ratio of phenolic compounds to aldehyde compounds is 1:2, it can ensure that there is enough formaldehyde to react with the phenolic compounds to form a highly cross-linked phenolic resin network. Deionized water mainly plays the role of a solvent in the synthesis of phenolic resin, helping phenolic and aldehyde compounds to mix evenly, and also participates in the polycondensation reaction. The role of the catalyst is to accelerate the polycondensation reaction, so its dosage is very small. Within the molar ratio range of 0.001 to 0.05, the catalyst can effectively promote the reaction between phenolic compounds and aldehyde compounds while maintaining the chemical structure and physical properties of the reaction product.
[0069] As an example, the molar ratio is 1:2:20:0.001, 1:2:20:0.008, 1:2:20:0.015, 1:2:20:0.022, 1:2:20:0.029, 1:2:20:0.036, 1:2:20:0.043, 1:2:20:0.05, etc.
[0070] In some embodiments of the present invention, when the mixed solution is reacted with the phenol-formaldehyde sol, the volume ratio of the mixed solution to the phenol-formaldehyde sol is 3: 1. Thus, the pores inside the carbon microspheres can be further increased, which is beneficial to improving the sodium storage capacity.
[0071] In some embodiments of the present invention, the gel microspheres are subjected to a carbonization reaction to form phenolic resin carbon microspheres, and the carbonization reaction temperature is 1000-1600° C. Further, the carbonization reaction temperature is 1300-1600° C. The carbonization reaction time is 2-8 hours. Further, the carbonization reaction time is 3-5 hours.
[0072] During the carbonization reaction, the pore shrinkage of the carbon microspheres is regulated by controlling the carbonization reaction temperature and time, thereby changing the closed pore volume of the carbon microspheres.
[0073] In some embodiments of the present invention, the surfactant is at least one of Span-80, Pluronic F127, and Pluronic F108.
[0074] In some embodiments of the present invention, the catalyst is at least one of sodium carbonate, ammonia water and sodium hydroxide. Further, the catalyst is sodium carbonate.
[0075] In a second aspect of the embodiment of the present invention, the present invention provides a phenolic resin carbon microsphere obtained by the preparation method of the first aspect, and the phenolic resin carbon microsphere satisfies at least one of the following:
[0076] (a) The specific surface area of phenolic resin carbon microspheres is 2 to 10 m 2 / g;
[0077] (b) The true density of phenolic resin carbon microspheres is 1.5-1.9 g / cm 3 ;
[0078] (c) The particle size of phenolic resin carbon microspheres is 2 to 15 μm.
[0079] The phenolic resin carbon microspheres of the present invention have a small specific surface area, low density and small particle size, indicating that the carbon microspheres have a rich closed-pore structure and are suitable as negative electrode materials for sodium ion batteries. The carbon microspheres with a small specific surface area have less surface reaction when the battery is first charged, avoiding excessive consumption of positive electrode sodium ions and resulting in a decrease in the first efficiency. The presence of closed pores provides abundant storage sites for the embedding and de-embedding of sodium ions, especially when the true density is 1.6 to 1.8 g / cm 3 When the sodium ion storage capacity is increased, the phenolic resin carbon microspheres can effectively increase the sodium ion storage capacity. Therefore, the phenolic resin carbon microspheres as the negative electrode material of the sodium ion battery have a high reversible specific sodium storage capacity, good cycle stability and rate performance.
[0080] As an example, the specific surface area is 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, etc.
[0081] As an example, the true density is 1.5 g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 .
[0082] As examples, the particle sizes are 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, etc.
[0083] In a third aspect of the embodiments of the present invention, the present invention provides a negative electrode material for a sodium ion battery, comprising the phenolic resin carbon microspheres obtained by the preparation method of the first aspect, or comprising the phenolic resin carbon microspheres of the second aspect.
[0084] Therefore, the sodium ion battery negative electrode material of the present invention can significantly improve the cycle stability and rate performance of the battery.
[0085] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0086] Embodiment 1:
[0087] A method for preparing phenolic resin carbon microspheres, the steps are as follows:
[0088] (1) 8.808 g of resorcinol, 11.2 mL of formaldehyde, 30 mL of deionized water, and 0.0848 g of sodium carbonate were weighed in a molar ratio of 1:2:20:0.01, and the mixture was stirred at room temperature for 15 min to obtain a golden yellow resorcinol-formaldehyde sol;
[0089] (2) weighing 2 mL of surfactant Span-80 and 98 mL of cyclohexane at a volume ratio of 1:49, and stirring at a speed of 400 rpm / min to form a uniform mixed solution;
[0090] (3) adding 33 mL of resorcinol-formaldehyde sol to the mixed solution at a volume ratio of 3:1, continuing stirring and reacting in a 25° C. water bath for 72 h, using acetone to remove Span-80 in the reaction product to obtain wet gel microspheres, and then drying at room temperature and pressure;
[0091] (4) The dried gel microspheres were carbonized at 1500°C for 3 h under nitrogen protection to obtain phenolic resin carbon microspheres (such as Figure 1 shown).
[0092] Embodiment 2:
[0093] The difference between Example 2 and Example 1 is as follows: in step (2) of Example 2, the volume ratio of surfactant Span-80 and cyclohexane is 1:9, and the mixing and stirring speed is 200 rpm / min; the water bath temperature in step (3) is 50°C; and the carbonization treatment in step (4) is a carbonization reaction at 1300°C for 6 hours.
[0094] Embodiment 3:
[0095] The difference between Example 3 and Example 1 is that in step (2) of Example 3, the volume ratio of surfactant Span-80 and cyclohexane is 1:16, and the mixing and stirring speed is 1000 rpm / min; the water bath temperature in step (3) is 35°C; and the carbonization treatment in step (4) is a carbonization reaction at 1600°C for 2h.
[0096] Embodiment 4:
[0097] The difference between Example 4 and Example 1 is that the water bath temperature in step (3) of Example 4 is 48° C.; the carbonization treatment in step (4) is a carbonization reaction at 1300° C. for 6 h.
[0098] Embodiment 5:
[0099] The difference between Example 5 and Example 1 is that the water bath temperature in step (3) of Example 5 is 100° C.; the carbonization reaction time in step (4) is 4 h.
[0100] Embodiment 6:
[0101] The difference between Example 6 and Example 1 is that the water bath temperature in step (3) of Example 6 is 35° C. and the water bath time is 120 h; the carbonization treatment in step (4) is a carbonization reaction at 1600° C. for 4 h.
[0102] Embodiment 7:
[0103] The difference between Example 7 and Example 1 is as follows: the water bath temperature in step (3) of Example 7 is 100° C. and the water bath time is 150 h; the carbonization treatment in step (4) is a carbonization reaction at 1600° C. for 2 h.
[0104] Embodiment 8:
[0105] The difference between Example 7 and Example 1 is that the water bath temperature in step (3) of Example 7 is 35° C.; the carbonization treatment in step (4) is a carbonization reaction at 1400° C. for 4 hours.
[0106] Embodiment 9:
[0107] The difference between Example 9 and Example 5 is that the phenolic compound in step (1) of Example 9 is phloroglucinol; the water bath temperature in step (3) is 48° C., and the water bath time is 36 h.
[0108] Physical and chemical performance test:
[0109] 1. Test content
[0110] 1. Structural testing
[0111] The appearance morphology of the prepared phenolic resin carbon microspheres was tested using a scanning electron microscope (SEM); the particle size and particle size distribution of the phenolic resin carbon microspheres were tested using a laser particle size analyzer; and the specific surface area of the phenolic resin carbon microspheres was tested using a specific surface area tester.
[0112] 2. Electrochemical performance test
[0113] The prepared phenolic resin carbon microspheres were prepared as working electrodes according to the mass ratio of phenolic resin carbon microspheres: conductive agent acetylene black: polyvinylidene fluoride = 80:10:10, and the metal sodium sheet was used as the counter electrode. Then, ethylene carbonate EC and diethyl carbonate DEC were mixed in a volume ratio of 1:1, and sodium hexafluorophosphate NaPF6 was added to prepare an electrolyte containing 1M sodium hexafluorophosphate NaPF6, and the above components were assembled into a sodium ion battery. The cycle performance and rate performance of the sodium ion battery were tested. The test temperature was 25°C and the test voltage was 0.01~2.8V.
[0114] 2. Test Results
[0115] 1. Structural test results
[0116] The structural test results of the phenolic resin carbon microspheres of Examples 1-9 are shown in Table 1.
[0117] Table 1 Structural test results of phenolic resin carbon microspheres of Examples 1-9
[0118]
[0119] The scanning electron microscopy (SEM) results of the phenolic resin carbon microspheres of Example 1 are shown in Figure 1 , particle size distribution see Figure 2 ; The particle size distribution of the phenolic resin carbon microspheres of Example 2 is shown in Figure 5 ; The particle size distribution of the phenolic resin carbon microspheres of Example 3 is shown in Figure 6 .Depend on Figure 1 It can be seen that the phenolic resin carbon microspheres prepared in the present invention have a smooth surface and do not shrink, break, or sink after drying and carbonization at normal pressure and temperature.
[0120] As shown in Table 1, in the preparation method of the phenolic resin carbon microspheres of the present invention, the size, particle size distribution, specific surface area and other structural characteristics of the carbon microspheres can be adjusted by changing the water bath temperature and time during the cross-linking reaction, as well as the temperature and time of the carbonization reaction. The phenolic resin carbon microspheres of the present invention have a narrow particle size distribution, a small particle size, a small specific surface area, and a low true density, indicating that the carbon microspheres have abundant internal pores, which is conducive to sodium storage. Therefore, it is shown that the phenolic resin carbon microspheres of the present invention can provide more sites for the storage of sodium ions, which is conducive to improving the sodium storage capacity.
[0121] 2. Electrochemical performance test results
[0122] The electrochemical performance test results of the phenolic resin carbon microspheres of Examples 1-9 are shown in Table 2.
[0123] Table 2 Electrochemical performance test results of phenolic resin carbon microspheres of Examples 1-9
[0124]
[0125]
[0126] As shown in Table 2, at a current density of 0.05A / g, the reversible capacity of the phenolic resin carbon microspheres of the present invention as the negative electrode material of the sodium ion battery is 220-325mAh / g, and the first efficiency is 74-82%; at a current density of 0.5A / g, the reversible capacity is 145-230mAh / g. This shows that the phenolic resin carbon microspheres of the present invention have excellent reversible specific capacity and first efficiency.
[0127] Depend on Figure 3 and Figure 4 It can be seen that the phenolic resin carbon microspheres of the present invention have good cycle stability and rate performance.
[0128] Therefore, it is shown that the phenolic resin carbon microspheres of the present invention have excellent reversible specific capacity, good cycle stability and rate performance as the negative electrode material of sodium ion batteries.
[0129] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0130] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing phenolic resin carbon microspheres, characterized in that: The following steps are involved: mixing a phenolic compound, an aldehyde compound, water and a catalyst to form a phenol-aldehyde sol; mixing a surfactant and cyclohexane to form a mixed solution; The mixed solution is reacted with the phenol-formaldehyde sol at a reaction temperature of 25 to 100° C. for a reaction time of 36 to 200 hours to form gel microspheres, and then dried; The dried gel microspheres are subjected to carbonization reaction to form phenolic resin carbon microspheres.
2. The preparation method according to claim 1, characterized in that: The phenolic compound includes at least one of resorcinol and phloroglucinol.
3. The preparation method according to claim 1, characterized in that: The drying process is drying at room temperature and pressure.
4. The preparation method according to claim 1, characterized in that: In the process of mixing the surfactant and cyclohexane to form a mixed solution, the control parameters are: (1) The speed during mixing is 50-1000 r / min; (2) The volume ratio of the surfactant to the cyclohexane is (1:9) to (1:49).
5. The preparation method according to claim 1, characterized in that: The aldehyde compound includes at least one of formaldehyde, benzaldehyde and acetaldehyde.
6. The preparation method according to claim 1, characterized in that: In the phenol-formaldehyde sol, the molar ratio of the phenol compound, the aldehyde compound, the deionized water and the catalyst is 1:2:20:(0.001-0.05).
7. The preparation method according to claim 1, characterized in that: In the reaction of the mixed solution with the phenol-formaldehyde sol, the volume ratio of the mixed solution to the phenol-formaldehyde sol is 3:
1.
8. The preparation method according to claim 1, characterized in that: The dried gel microspheres are subjected to carbonization reaction to form phenolic resin carbon microspheres, and the temperature of the carbonization reaction is 1000-1600° C. and the time is 2-8 hours.
9. A phenolic resin carbon microsphere obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The phenolic resin carbon microspheres meet at least one of the following requirements: (a) The specific surface area of the phenolic resin carbon microspheres is 2 to 10 m 2 / g; (b) The true density of the phenolic resin carbon microspheres is 1.5 to 1.9 g / cm 3 ; (c) The particle size of the phenolic resin carbon microspheres is 2 to 15 μm.
10. A negative electrode material for a sodium ion battery, characterized in that: The invention comprises phenolic resin carbon microspheres obtained by the preparation method according to any one of claims 1 to 8, or comprises phenolic resin carbon microspheres according to claim 9.